1994
DOI: 10.1002/1097-4679(199409)50:5<681::aid-jclp2270500504>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of trauma: Post-traumatic stress among civilian internees of the japanese during world war II

Abstract: This study examined predictors and health‐related effects of post‐traumatic stress among 129 civilian internees of the Japanese during World War II. Post‐traumatic stress disorder was noted in 36.7% within the 6 months after their release and in 15.0% within the most recent 6 months. Women were more likely than men to indicate post‐traumatic stress disorder within the 6 months after their release. Higher incomes were associated with lower levels of post‐traumatic stress within the most recent 6 months. After c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…One is that time is a healer: as the years pass, any detrimental impact of captivity will weaken, and more ex-POWs will recover partly or in full. This view is supported by previous findings of declines in the levels of depression and anxiety among former POWs after approximately a decade (Tennant, Fairley, Dent, Sulway, & Broe, 1997), as well as findings of fewer PTSD symptoms some 50 years after captivity than in the first year post-captivity, as reported retrospectively (Engdahl, Speed, Eberly, & Schwartz, 1991;Potts, 1994).…”
Section: Trajectories Of Captivity-induced Ptsdsupporting
confidence: 80%
See 1 more Smart Citation
“…One is that time is a healer: as the years pass, any detrimental impact of captivity will weaken, and more ex-POWs will recover partly or in full. This view is supported by previous findings of declines in the levels of depression and anxiety among former POWs after approximately a decade (Tennant, Fairley, Dent, Sulway, & Broe, 1997), as well as findings of fewer PTSD symptoms some 50 years after captivity than in the first year post-captivity, as reported retrospectively (Engdahl, Speed, Eberly, & Schwartz, 1991;Potts, 1994).…”
Section: Trajectories Of Captivity-induced Ptsdsupporting
confidence: 80%
“…The rates are higher than the PTSD rates of 5% (Tennant et al, 1997) and 15% (Potts, 1994) that were found among American POWs in World War II several decades postwar, but those rates are on the low end. Most reports of World War II POWs note rates of 30-76% 40-50 years postwar (Speed, Engdahl, Schwartz, & Eberly, 1989;Sutker & Allain, 1996;Zeiss & Dickman, 1989).…”
Section: Controlsmentioning
confidence: 57%
“…The increase in PTSD in the ex-POWs is consistent with the findings of increased PTSD rates and symptom level over a 4-year measurement interval among older American ex-POWs, 6 but differs from findings of reports of decreased PTSD symptoms over time. 10,11 The differences are probably related to the times of measurement. A previous study 6 found a U-curve pattern, with high PTSD rates immediately after captivity, followed by a gradual decline and then, from midlife onward, a rise in rates.…”
Section: Changes Over Timementioning
confidence: 99%
“…This view is supported by previous findings of declines in the levels of depression and anxiety among former POWs after approximately a decade, 9 as well as findings of fewer PTSD symptoms some 50 years after captivity than in the first year postcaptivity, as reported retrospectively. 10,11 The second view is that PTSD is a chronic ailment, in which symptoms will intensify with the passage of time, with the natural decline in the individual's physical and mental condition over the years. This view gains some support from a recent study that found increased PTSD over a 4-year period among former American POWs.…”
mentioning
confidence: 99%
“…Comparable research in civilian populations has lagged behind, partly due to the relative lack of large databases of medical records. A notable exception is the work that has been done to study the effects of concentration camp experiences in the Holocaust and Japanese-American internment in the United States during World War II (Favaro, 1999;Kuch, 1992;Potts, 1994).…”
Section: Introductionmentioning
confidence: 99%